In vitro cytotoxic potential of Gymnema sylvestre fractions on HT-29 cell line - Arumugam, Shanmugapriya; Yadav, Sangilimuthu Alagar; Krishnan, Abinaya; Manoharan, Sowmya Priya; Gnanaselvan, Suvathika (Journal of Phytology, 2022)
The HT-29 colon cancer cell line was used in the current work to investigate the anti-cancer efficacy of Gymnema sylvestre extracts. The viability, apoptosis, flow cytometry, and mode of action of the active fraction were also evaluated. The active fractions of G. sylvestre caused cell cycle arrest at the S phase and G2/M phase, and also caused programmed cell death. The alcoholic fractions showed anti-cancer effect in HT-29 cancer cells. By applying methanolic fraction of Gymnema sylvestre to the HT-29 cells, IC50 was observed at 140.39 μg/mL, whereas for chloroform fraction of Gymnema sylvestre showed IC50 at 154.44 μg/mL. The herbal extract for colon cancer treatment may be developed with the help of researchers due to G. sylvestre’s anti-cancer properties.